The Impact of Motivation on The Performance of Employees in Hotel Sapadia Pematangsiantar - Marto Silalahi; Sudung Simatupang; Yosi Anindhita Molek Manalu (Journal of Social Science, 2021)
The concept of this study aims to examine the effect of motivation on the performance of employees of Hotel Sapadia Pematangsiantar, amounting to 42 people with research time in April 2020. The study was conducted with qualitative and quantitative analysis. The results of the validity test show that the calculated r value is greater than critical r with the results of the research variable being declared valid, the reliability test shows that all research variables are declared reliable. Then, the determination coefficient test shows that the R value has a strong and positive relationship with motivation and employee performance and motivation variable is able to explain and measure employee work variable. The results of the normality test explain that the research is normally distributed. The simple equation regression equation shows positive results of motivation on employee performance and the hypothesis test accepts the hypothesis of the study.